OP0064 Joint EULAR/ERA-EDTA recommendations for the management of adult and pediatric lupus nephritis. (23rd January 2014) - Bertsias, G.; Tektonidou, M.; Amoura, Z.; Aringer, M.; Bajema, I.; Berden, J.; Boletis, J.; Cervera, R.; Dörner, T.; Doria, A.; Ferrario, F.; Flöge, J.; et al.
Abstract : Background: There is increasing evidence from clinical trials on which to base a rational approach to the care of lupus nephritis (LN). Objectives: To develop recommendations for the management of LN. Methods: Questions were compiled using a modified Delphi technique. A systematic PubMed search was performed, and evidence-based and expert-opinion approach was followed to prepare recommendations. Results: No clinical, serologic or laboratory tests can accurately predict renal biopsy findings in SLE; any sign of renal involvement, especially proteinuria >0.5 g/24-hr, should be an indication for biopsy. Assessment should include glomerular changes, activity and chronicity indices, tubulointerstitial lesions, and vascular lesions. Because of more favourable efficacy/toxicity ratio, for most patients with ISN/RPS2003 Class IIIA or A/C and Class IVA or A/C (±V) LN, mycophenolate mofetil (MMF) or low-dose intravenous cyclophosphamide (CY) in combination with glucocorticoids is recommended. Induction regimens should be combined initially with three daily pulses of IV methylprednisolone, followed by oral prednisolone 0.5 mg/kg/day. In patients with adverse clinical or histological features, CY can also be prescribed monthly at higher doses (0.75-1g/m 2 ) for 6 months or orally for 3 months. For pure class V disease with nephrotic-range proteinuria, MMF in combination with oral prednisolone may be used initially. In patients responding to initial therapy (≥50% reduction in proteinuria and stable/improved GFR) within 6-12 months, maintenance immunosuppression is recommended with MMF or azathioprine for at least 3 years. For MMF or CY failures, we recommend switching to the other or rituximab. Pregnancy should be planned in stable patients with inactive lupus and serum creatinine <2 mg/dL. The intensity of treatment should not be reduced in anticipation of pregnancy. Nephritis is more frequent at presentation in children with SLE and its diagnosis, management, and monitoring is similar to that in adults. Conclusions: Recommendations for LN were developed using an evidence-based approach followed by expert consensus. Disclosure of Interest: None Declared